(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Delhiis famous for its Universities, Colleges and Study. Delhi has lots of academic colleges. There are some independent women colleges alsoand those are working for women empowerment. This study is restricted for 18 women colleges, which provide educationin different disciplines. Most of theseare high profile. Some are very old andadopted by Indian heritage. Some arefamous for their infrastructure. In this changing scenario education isshifting from print media to electronic media, which is in the form ofInternet. It is difficult to defineInternet comprehensively. Now-a-daysInternet has become an effective tool for teaching and learning. Internet is a platform for providing andsharing information. When two computersare connected over the Internet they can send and receive all kinds ofinformation such as text, graphics, voice, video and all computer program. Internet is a pool of information contributedby more than 100 countries and it is apowerful dissemination tool. It helps usto keep up-to-date with current development and overcomes the problems of delay in publication of paper media andlimited clientele. Internet is means offaster communication through e-mail, teleconferencing, e-journals, searchengines, employment searches and discussion forums etc. The term of Internet denotes network ofseveral computer networks. It is agrouping of mission of computer networks inter-connected with each other’s,reaching billions of people around the globe. It was originally designed for US Defense Commission Network ‘ARPANET’.Today Internet has become – one of the most important modes ofcommunication. People in every walk oflife, such as education, management, business, medicine, defense, banking etc.are using Internet. Within the last tenyears, Internet has become global and ubiquitous. It reaches in hundreds of countries and is featured daily in the all walks oflife. The Internet provides instantaccess to billions of information sources such as books, journals, indexes,abstracts, video recordings, sound recordings etc. Unlike single book sources, Internet informationis accessible to multiple users at the same time. There are reportedly three new pages added tothe Internet every second of the day. There are a lot of material. Internet is considered as a great information source to the academic andresearch community of the colleges of Delhi University. Internet is changing the process ofknowledge creation and dissemination. ininformation technology is fastestcommunication tool for generation, gathering, and disseminationof Information. Information revolutionnot only supplies the technological horsepower that drives the wen, but fuelsan unprecedented demand for storing, organizing, disseminating, and accessinginformation. Information is being sharedby many areas through the use of Internet. Today large numbers of information sources are available on theInternet. Technology has changed toXeroxing, Fax, Reprography, CD-ROM, PEN drive and other electronic materialfrom print material. It has becomedifficult to say, what is not available on the Internet. It will not be surprising of in the nearfuture the Internet connectivity becomes a necessity of life just likeconnection to water tap, electricity and telephone in all the countriesirrespective of their social-economic status. Govt. of India is working for various projects where they areencouraging people to more and moreInternet use. Delhi University isproviding Internet connectivity to its students free of cost through DelhiUniversity Library Science Network (DULS), which is restricted to DelhiUniversity only by specific and unique ID. India is always famous for itsstudy. Earlier time it was known for itsGurukul and Guru-Shishya parampara, which has been shifted to Internet Yug now.